1985
DOI: 10.1111/j.1365-2621.1985.tb10477.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of Microbial Spoilage on Fresh Poultry using a Combination Potassium Sorbate/Carbon Dioxide Packaging System

Abstract: The effects of potassium sorbate combined with vacuum or carbon dioxide modified atmosphere packaging on natural poultry spoilage flora were examined. Fresh chicken thighs were dipped into either 2.5% potassium sorbate solution or distilled water, adjusted to pH 6.0 and packaged on trays in Nylon/Plexar/Surlyn bags. Atmospheres of either air, vacuum or 100% CO2 were created in the packages which were then stored at 10 2 1°C for 10 days. Changes in aerobic plate counts, lactic acid bacteria and pseudomonads wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…These observations are consistent with those reported by Baker et al (1985); who found that after 7 days storage of chicken tissue at 2C, 20% CO, was as effective as higher C02 levels in inhibiting bacteria, whereas after 28 days, 80% CO, was needed to keep the microbial load below log,, 8.0ig. In general, data reported here are in agreement with those reported by other investigators, who found that lactobacilli were predominant under MAP conditions, whereas Pseudomoms were the prevailing organisms responsible for the spoilage of poultry meat during storage in air atmosphere (Bailey et al 1979;Robach 1979;Beyer and Sinell 1981;Dainty et al 1983;Mcmeekin et al 1984;Elliot et al 1985;Studer et u1. 1988;Zeitoun and Debevere 1992).…”
Section: Pseudomonassupporting
confidence: 92%
“…These observations are consistent with those reported by Baker et al (1985); who found that after 7 days storage of chicken tissue at 2C, 20% CO, was as effective as higher C02 levels in inhibiting bacteria, whereas after 28 days, 80% CO, was needed to keep the microbial load below log,, 8.0ig. In general, data reported here are in agreement with those reported by other investigators, who found that lactobacilli were predominant under MAP conditions, whereas Pseudomoms were the prevailing organisms responsible for the spoilage of poultry meat during storage in air atmosphere (Bailey et al 1979;Robach 1979;Beyer and Sinell 1981;Dainty et al 1983;Mcmeekin et al 1984;Elliot et al 1985;Studer et u1. 1988;Zeitoun and Debevere 1992).…”
Section: Pseudomonassupporting
confidence: 92%
“…Thus, 9 log cfu/g corresponded to 8.16 log cfu/cm 2 . Other authors have reported spoilage odors in poultry when counts approached 7-8 cfu/cm 2 (Barnes, 1976;Elliot et al, 1985;Studer, Schmidt, Gallo, & Schmidt, 1988).…”
Section: Resultsmentioning
confidence: 93%
“…Furthermore, its greater solubility extends the use of sorbate to solutions appropriate for dipping and spraying (Thomas, 2000). Potassium sorbate has been extensively investigated as an antimicrobial agent for use in meat including poultry to extend its shelf life and inhibit the growth of pathogens such as Salmonella or Staphylococcus aureus (Ahmed et al, 2003;Elliot, Tomlins, & Gray, 1985;Robach & Sofos, 1982;To & Robach, 1980). Moreover, eVective concentrations do not aVect sensory characteristics of poultry (Cunningham, 1979).…”
Section: Introductionmentioning
confidence: 97%
“…Pseudomonas species are considered the main spoilage microorganisms of refrigerated (1 to 4 °C) poultry meat under aerobic condition (Arnaut‐Rollier and others 1999; Mead 2004). They are also the primary bacteria population found on spoiled refrigerated meat and poultry flesh during storage in air (Elliott and others 1985; Russell and others 1996). Metabolically, the spoilage Pseudomonas species have relatively extensive oxidative capabilities and can readily utilize a variety of soluble, low molecular weight nitrogenous compounds as an energy source (ASM, 2007).…”
Section: Introductionmentioning
confidence: 99%